Prenatal Immune Challenge in Mice Leads to Partly Sex-Dependent Behavioral, Microglial, and Molecular Abnormalities Associated with Schizophrenia - Hui, Chin W.; St-Pierre, Abygaël; El Hajj, Hassan; Remy, Yvan; Hébert, Sébastien S.; Luheshi, Giamal N.; Srivastava, Lalit K.; Tremblay, Marie-Ève (Frontiers in Molecular Neuroscience, 2018)
Epidemiological studies revealed that environmental factors comprising prenatal infection are strongly linked to risk for later development of neuropsychiatric disorders such as schizophrenia. Considering strong sex differences in schizophrenia and its increased prevalence in males, we designed a methodological approach to investigate possible sex differences in pathophysiological mechanisms. Prenatal immune challenge was modeled by systemic administration of the viral mimic polyinosinic-polycytidylic acid (Poly I:C) to C57BL/6 mice at embryonic day 9.5. The consequences on behavior, gene expression, and microglia –brain immune cells that are critical for normal development– were characterized in male versus female offspring at adulthood. The cerebral cortex, hippocampus, and cerebellum, regions where structural and functional alterations were mainly described in schizophrenia patients, were selected for cellular and molecular analyses. Confocal and electron microscopy revealed most pronounced differences in microglial distribution, arborization, cellular stress, and synaptic interactions in the hippocampus of male versus female offspring exposed to Poly I:C. Sex differences in microglia were also measured under both steady-state and Poly I:C conditions. These microglial alterations were accompanied by behavioral impairment, affecting for instance sensorimotor gating, in males. Consistent with these results, increased expression of genes related to inflammation was measured in cerebral cortex and hippocampus of males challenged with Poly I:C. Overall, these findings suggest that schizophrenia’s higher incidence in males might be associated, among other mechanisms, with an increased microglial reactivity to prenatal immune challenges, hence determining disease outcomes into adulthood.